Pemanfaatan Smart Tree Photosyntesis untuk Meningkatkan Hasil Belajar IPA Siswa Kelas V SDN 11 Air Kalam - Nelli Herawani; Hadiyanto Hadiyanto (Pedagogi: Jurnal Ilmu Pendidikan, 2019)
This study aims to describe the utilization of Smart Tree Photosynthesis media in science learning in grade V primary school. This research begins from the low learning outcomes of students of class V SDN 11 Air Kalam in science learning with abstract materials. The reason for teachers using more abstract material because the school did not have the appropriate media for learning these materials. Students were uninterested, less motivated, and the learning process did not provide a meaningful experience to students. So the learning outcomes did not reach the specified target. In the early study of science learning with photosynthesis material, only 5 of 33 students who achieve mastery of 70%. The author makes three-dimensional media Smart Tree Photosynthesis as one solution to solve the problem. Based on the results of reflection on two cycles, it can be seen that there was a better activity of student learning outcomes. The grade average value reached 85.76 after the evaluation. So, it can be concluded that the utilization of three dimensions of Smart Tree Photosynthesis media in science learning with the material of making food on green plants is able to improve student learning outcomes, and the lesson presented by the teacher is more meaningful for the students.